Kajian Pembagian Waris dan Wasiat Perspektif Hadis - Putri Maharani Pratama (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss wills according to hadith. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about wills in the history of Tirmidhi No. 2048. The results and discussion of this study indicate that the status of quality hadith hasan li ghairihi fulfills the qualifications of maqbul ma'mul bih for Islamic experience. This study concludes that the hadith narrated by Tirmidhi No. 2048 is relevant to be used as motivation in developing public knowledge regarding the provisions of the distribution of inheritance and wills.